Odpowiedzi

2010-04-09T15:34:36+02:00
A) P=mF (F)
F=P/m
b)E=mgh (h)
h=E/mg
c) y=O,25x (x)
x=y/0,25
d) y=2t-1 (t)
y+1=2t
t=(y+1)/2
e)K=1/4n (n) /*4
4K=n
f) K=a/R (R) //*R
KR=a
R=a/K
2010-04-09T15:38:03+02:00
A)P=mF |:m
P/m=F
b)E=mgh |:mg
E/mg=h
c)y=0,25x |*4
4y=x
d)y=2t-1 |+1
y+1=2t |:2
y+1/2=t
e)K=1/4n |*4
4K=n
f)K=a/R |:a
K/a=R
  • 8650
  • Rozwiązujący
2010-04-09T15:44:11+02:00
A)P=mF (F)
P=mF /:m
P:m=F
F=P:m
b)E=mgh (h)
E=mgh /:mg
E:mg=h
h=E:mg
c)y=0,25x (x)
y=0,25x /:0,25
4y=x
x=4y
d) y=2t-1 (t)
2t=y-1 /:2
t=(y-1):2
e)K=1/4n (n)
K=1/4n /:4
1/4 K=1/4:n
n=1/4:1/4K
f)K=a/R (R)
K=a/R
a:K=R
R=a/K